Antioxidant and anti‐inflammatory effects of the monocarbonyl curcumin analogs B2BRBC and C66 in monocrotaline‐induced right ventricular hypertrophy. Issue 8 (10th June 2019) - Hadzi‐Petrushev, Nikola; Angelovski, Marija; Rebok, Katerina; Mitrokhin, Vadim; Kamkin, Andre; Mladenov, Mitko
Abstract: For 22 days after monocrotaline injection two groups of rats received either of the monocarbonyl curcumin analogs (2E, 6E)‐2, 6‐bis(2‐bromobenzylidene)cycloxehanone (B2BrBC) and (2E, 6E)‐2, 6‐bis([2‐triﬂuoromethyl]benzylidene)cyclohexanone (C66), and their right ventricle parameters were compared to those from the control and the monocrotaline injected animals. B2BrBC and C66 treatments did not prevent the monocrotaline‐induced right ventricular hypertrophy but attenuated the changes in antioxidant enzyme activities and reduced inflammation. The level of thiol‐based nonenzymatic antioxidants did not change in the function of monocrotaline or curcumin analogs treatment. However, due to its stronger antioxidant properties, only B2BrBC treatment was effective in the reduction of monocrotaline‐associated lipid peroxidation. The obtained results suggest that increasing the levels of antioxidant enzymes may not be sufficient to reduce oxidative stress and chronic inflammation optimally and our current study supports the potential of compounds with more than one beneficial biological activity as a promising treatment against the progression of cardiac hypertrophy.